2005
DOI: 10.1038/ni1239
|View full text |Cite
|
Sign up to set email alerts
|

Sustained localized expression of ligand for the activating NKG2D receptor impairs natural cytotoxicity in vivo and reduces tumor immunosurveillance

Abstract: Upregulation of the inducible gene products MICA (human) and Rae-1 (mouse) may promote tumor surveillance and autoimmunity by engaging the activating receptor NKG2D on natural killer (NK) cells and T cells. Nevertheless, sustained expression of MICA by tumors can also elicit NKG2D downregulation, perhaps indicating 'immunoevasion'. Investigating this paradox, we report here that constitutive Rae-1epsilon transgene expression in normal epithelium elicited local and systemic NKG2D downregulation, generalized but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
350
6
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 392 publications
(389 citation statements)
references
References 49 publications
31
350
6
2
Order By: Relevance
“…100 Importantly, this strategy must be examined with scrutiny because sustained exposure of NKG2D ligands, either membrane-bound or in soluble form, to their receptor results in reduced NKG2D expression and impaired NK cell killing capacity. [102][103][104] Finally, several cytokines (for example, IFN-a, IL-15, TGF-b) were demonstrated to affect NKG2D ligand expression, but have not been tested on AML cells. 4,84 The proteasome inhibitor bortezomib and the histone deacetylase inhibitor depsipeptide were also shown to improve NK-cellmediated killing of AML cells through the death-receptor pathway TNF-related apoptosis-inducing ligand (TRAIL).…”
Section: Nk Cell Immune Escape In Aml E Lion Et Almentioning
confidence: 99%
“…100 Importantly, this strategy must be examined with scrutiny because sustained exposure of NKG2D ligands, either membrane-bound or in soluble form, to their receptor results in reduced NKG2D expression and impaired NK cell killing capacity. [102][103][104] Finally, several cytokines (for example, IFN-a, IL-15, TGF-b) were demonstrated to affect NKG2D ligand expression, but have not been tested on AML cells. 4,84 The proteasome inhibitor bortezomib and the histone deacetylase inhibitor depsipeptide were also shown to improve NK-cellmediated killing of AML cells through the death-receptor pathway TNF-related apoptosis-inducing ligand (TRAIL).…”
Section: Nk Cell Immune Escape In Aml E Lion Et Almentioning
confidence: 99%
“…Mechanisms such as shedding of ligands, chronic ligand exposure, and trogocytosis have been described (30,31,39,40). Interestingly, CD96, a NK cell receptor that like DNAM-1 binds CD155, was shown to be down-regulated upon ligand engagement (41).…”
Section: Tumor-associated Nk Cells Fail To Target Autologous Tumor Cementioning
confidence: 99%
“…20,21 Thus, it is possible that sustained engagement of NKG2D by iMICA protein might decrease the expression of NKG2D on the surface of NK cells. However, we found that the expression of NKG2D in NK cells activated for 1 week did not decrease when compared with freshly isolated NK cells (Figure 1e).…”
Section: Mica Synergizes With Ilmentioning
confidence: 99%